Hydrology controls dissolved organic matter export and composition in an Alpine stream and its hyporheic zone. (1st December 2015) - Fasching, Christina; Ulseth, Amber J.; Schelker, Jakob; Steniczka, Gertraud; Battin, Tom J.
Abstract: Streams and rivers transport dissolved organic matter (DOM) from the terrestrial environment to downstream ecosystems. In light of climate and global change it is crucial to understand the temporal dynamics of DOM concentration and composition, and its export fluxes from headwaters to larger downstream ecosystems. We monitored DOM concentration and composition based on a diurnal sampling design for 3 years in an Alpine headwater stream. We found hydrologic variability to control DOM composition and the coupling of DOM dynamics in the streamwater and the hyporheic zone. High‐flow events increased DOM inputs from terrestrial sources (as indicated by the contributions of humic‐ and fulvic‐like fluorescence), while summer baseflow enhanced the autochthonous imprint of DOM. Diurnal and seasonal patterns of DOM composition were likely induced by biological processes linked to temperature and photosynthetic active radiation (PAR). Floods frequently interrupted diurnal and seasonal patterns of DOM, which led to a decoupling of streamwater and hyporheic water DOM composition and delivery of aromatic and humic‐like DOM to the streamwater. Accordingly, DOM export fluxes were largely of terrigenous origin as indicated by optical properties. Our study highlights the relevance of hydrologic and seasonal dynamics for the origin, composition and fluxes of DOM in an Alpine headwater stream.